Social networking sites and their role in promoting beauty products for Iraqi women - Hamza Khaled Mutshar, Rese. (lark, 2024)
Social networking sites are among the most powerful tools and means used to promote in this era in general and for beauty products in particular, as these sites greatly affect the perception of beauty and self-confidence among Iraqi women, as these sites are used to publish promotional content and advertisements for beauty products and services, and provide A platform for Iraqi women to share and compare their photos and experiences in the field of beauty. Iraqi women may be exposed to beauty promotional content through these means constantly, and this is reflected in their perception of beauty, which leads to the development of unrealistic beauty standards that are not related to external appearance. Excessive use of social media may cause a decrease in the level of Low self-confidence among Iraqi women, as they may feel pressured to conform to the unrealistic aesthetic standards presented on these media. In his study, the researcher used the “descriptive approach,” relying on a questionnaire tool that was distributed to a sample of women who frequent beauty centers in Wasit Governorate. To obtain indicators and data and analyze them to determine the relationship between social networking sites and Iraqi women’s beauty products. The study concluded several results, most notably: 1- Iraqi women feel a lot of psychological pressure to have an ideal beauty appearance based on viewing social media platforms. 2- Social media platforms greatly reinforce unrealistic beauty standards among women. 3- Social networking sites negatively affect self-confidence and self-image when it comes to external appearance.